Guiding with wisdom: a model for early childhood sexual education classroom management - Nofridasari , Erlita Ayu; Hasanah, Enung (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2023)
Effective sex education plays a crucial role in providing children with a healthy understanding of sexuality, yet there persist various issues related to sex education in kindergarten. Classroom management challenges also represent significant obstacles that need to be addressed for the successful implementation of sex education. Within educational institutions like Ceria Timoho Kindergarten, the role of teachers in delivering sex education remains pivotal. This research aims to identify classroom management patterns used in providing sex education to children at Ceria Timoho Kindergarten through a qualitative approach involving observation, documentation, and interviews. Data analysis employed qualitative analysis methods. The research results reveal that the classroom management model for sex education emphasizes student-centric approaches that consider individual needs, holistic strategies encompassing emotional, social, and ethical aspects, the selection of age-appropriate teaching methods, the importance of effective communication, and the necessity for thorough evaluation to ensure age-appropriate understanding. These findings offer valuable insights into the significance of effective sex education in helping children comprehend and respect their sexuality, fostering emotional and physical awareness, and promoting overall well-being.